2008
DOI: 10.1001/archsurg.2007.66
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Recombinant Activated Factor VII in Major Surgical Procedures

Abstract: Treatment with rFVIIa is effective in reducing the rate of patients undergoing transfusion with allogeneic packed red blood cells. However, the cost-benefit ratio is favorable only in patients who need a huge number of packed red blood cell units. No safety concerns arise from the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 68 publications
(112 reference statements)
0
25
0
9
Order By: Relevance
“…A meta-analysis of seven randomized controlled trials of the safety and efficacy of rFVlIa in major surgical procedures concluded that treatment with rFVIIa was associated with reduced requirement of packed red cell transfusion, without any significant difference in thromboembolic complications or mortality rates [16]. Significant treatment benefit was only seen in patients receiving a dose of at least 50 mcg/kg body weight.…”
Section: Perioperative Blood Lossmentioning
confidence: 99%
“…A meta-analysis of seven randomized controlled trials of the safety and efficacy of rFVlIa in major surgical procedures concluded that treatment with rFVIIa was associated with reduced requirement of packed red cell transfusion, without any significant difference in thromboembolic complications or mortality rates [16]. Significant treatment benefit was only seen in patients receiving a dose of at least 50 mcg/kg body weight.…”
Section: Perioperative Blood Lossmentioning
confidence: 99%
“…Hemorragia. do rFVIIa induz formação de trombina e contribui para estabilidade da rede de fibrina no local da lesão vascular, resistente à fibrinólise precoce, além de contribuir para ativação plaquetária 9,12,13 . O uso de fator recombinante VII ativado (rFVIIa) na prática médica foi iniciado na década de 80 como agente pró-hemostático 2,9 .…”
Section: Abcddv/665unclassified
“…O uso de fator recombinante VII ativado (rFVIIa) na prática médica foi iniciado na década de 80 como agente pró-hemostático 2,9 . A US Food and Drugs Administration (FDA) licenciou o uso do rFVIIa em 25 de março de 1999 para profilaxia e tratamento de episódios de sangramento em pacientes com antecedente de hemofilia A ou B e inibidores de fator VIII e IX, mesmo após uso de fator VIII e IX (USA) 1,2,3,4,6,7,9,12,17,19 . Tem sido usado com sucesso em pacientes com hemofilia adquirida (anticorpos antifator VIII ou IX), deficiência de fator VII e trombastenia de Glanzmann refratários à reposição plaquetária (União Européia) 1,2,4,9,12,19 .…”
Section: Abcddv/665unclassified
See 2 more Smart Citations